KINETICS OF DEGRADATION PROCESS OF ORGANIC POLLUTANTS IN THE WATER OF CU DE RIVER, DA NANG CITY - Tu, Nguyen Thi Thanh; Sy, Phung Chi; Thang, Dinh Xuan (Vietnam Journal of Marine Science and Technology, 2014)
This article presents the research results on kinetics of the biochemical process of oxygen consumption in the Cu De river from May to July, 2012. This is one of the important processes in self-purification study and carrying capacity of biodegradable organic pollutants on the river basin. The experimental results were analysed base on pseudo-first order kinetic equation developed by Streeter &. Phelps. The correclated model was evaluated by using the Paired sample T-test method on the SPSS statistic analysis software. The results showed that the average biochemical rate coefficient had changed within 0.101- 0.122 per day and activation energy (E) equals was 5.56Kcal. This indicated that nature of the aboved degration process of organic pollution is a mineralization process of organic bonds.